Satellite cell contribution to disease pathology in Duchenne muscular dystrophy - Kodippili, Kasun; Rudnicki, Michael A. (Frontiers in Physiology, 2023)
Progressive muscle weakness and degeneration characterize Duchenne muscular dystrophy (DMD), a lethal, x-linked neuromuscular disorder that affects 1 in 5000 boys. Loss of dystrophin protein leads to recurrent muscle degeneration, progressive fibrosis, chronic inflammation, and dysfunction of skeletal muscle resident stem cells, called satellite cells. Unfortunately, there is currently no cure for DMD. In this mini review, we discuss how satellite cells in dystrophic muscle are functionally impaired, and how this contributes to the DMD pathology, and the tremendous potential of restoring endogenous satellite cell function as a viable treatment strategy to treat this debilitating and fatal disease.